The Impact of Entrepreneurial Orientation Success Factors to Muslim SME Success - Abdul Wahab, Nadratun Nafisah; Saedon, Muhammad Abdul Malik; Bulkia, Etmawati; Yahaya, Salimah; Rofie, Mohamad Khadafi (Selcuk University, 2020)
This study presentsa research of the multidimensional entrepreneurial orientation (innovation, risk and proactive) in relation to the Muslim SME success. Thus far, past literatures shown that limited study of Muslim SME success. This study was conducted in the form of survey, with data being gathered from 122 firms (operating above 3 years) selected through simple random sampling from 2286 Muslim SME in Malaysia. The results show that innovation and proactivefactors have relationshipsto SME Muslim success. The results shed new light on the theory and practice. This finding contributes toRBV theory and to the field of Islamic entrepreneurship focusing on Muslim SME success